The Resultant formula of Masses m_1/m_2,..., m_n in Space oxyz at a Point - Mahbod, Mohammad (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper, the formula of the contact resultant for masses (m-1,m-2,...,m-n) in space(oxyz) is calculated and proved. Regarding the importance of masses movement in space and their contact with each other, it is felt that in order to design and optimize dynamic systems (dynamic mechanics), a reasonable relation should be established between their subsets. This paper attempts to prove such a relation in the simplest possible way.